Julia Lopes de Almeida e a educação brasileira no fim do século XIX: um estudo sobre o livro escolar Contos infantis - Diana Vidal Gonçalves (Universidade do Minho, 2004)
The article intents to investigate the production of school books in Brazil, at the end of nineteen century. It begins by asking whether Julia Lopes de Almeida, famous Brazilian writer and feminist, is an intruder in the educational field or not. To answer the question the article explores Contos infantis, written by Julia and her sister Adelina Lopes Vieira, in its contents and structure. Then it analyses the story of their family, lived part in Brazil and part in Portugal. It concludes by claming attention to the importance of the confluence of these two approaches to understand the schooling projects existent in the Brazilian society at that time.